Making Household Crafts from Coconut Shells with Economic Value - Ahnaf Riyandirga Ariyansyah Putra Helmy; Ulfaizah Sahril Nurfadhilah; Ridwan Ridwan; Akmal Baharuddin; Noor Fadilah Romadhani (PT. Global Research Collaboration, 2024)
The use of coconut shells as a material for making household crafts has become a common practice in many tropical regions around the world. Coconut shells, the hard outer part of the coconut fruit, have a strong and durable texture, making them an ideal material for various types of craft products. One of the most common examples of coconut shell use is the production of cups, ladles, and ashtrays. Overall, the use of coconut shells as a material for creating household crafts such as cups, ladles, and ashtrays not only supports sustainable recycling practices but also creates unique products that showcase the beauty of nature. Skilled and creative artisans can produce a wide range of useful and attractive items from coconut shells, making them a valuable part of local culture and the craft industry.